The Quality of Indo-Pacific Bottlenose Dolphin (Tursiops aduncus) Sperm Following Liquid-storage in Low Temperature - Fahrudin, Mokhamad; Gusdinar, Rizal; Arifiantini, Raden Iis; Prasetyaningtyas, Wahono Esthi; Adnyane, I Ketut Mudite; Elmanaviean, Muhammad; Nugraha, Arifin Budiman; Karja, Ni Wayan Kurniani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Indo-Pacific bottlenose dolphin (Tursiops aduncus) is a marine mammal that lives in relatively small populations. The geographic ranges of this species are susceptible to the effects of human activities, thereby necessitating conservation efforts to prevent extinction. Therefore, this study aimed to evaluate the daily quality of dolphin sperm after several days of refrigeration. The sperm of two male dolphins were stored at 4oC for 4 days, and the quality was observed daily to determine the motility, viability, membrane integrity, and sperm abnormalities. Sperm samples were divided into four groups, consisting of two centrifuged followed by the removal of seminal plasma, and two groups without centrifugation, containing 100x106 and 200x106 sperm/ml each. After liquid storage, the motility of sperm was 63-75% with no significant reduction in the first 3 days. Sperm viability following storage was 65-75% and the percentage with abnormal morphology ranged from 2-6%. Furthermore, there was no significant increase in abnormal morphology of sperm on any day of storage for 3 days. Sperm membrane integrity was 36-49%, with no significant reduction in the membrane integrity in the first 2 days. There was no significant difference in sperm quality, although centrifugation and removal of seminal plasm had a slight effect. The results of this study showed that Indo-Pacific bottlenose dolphin sperm could be stored for a short period as liquid storage while maintaining a quality that allows for future use.